Provas de carga estática com carregamento lateral em estacas escavadas hélice contínua e cravadas metálicas em areia - Araújo, Arthur Gomes Dantas de (2013)
An experimental study has been conducted to investigate the behavior of continuous flight auger (cfa) bored piles and metalic driven H-section piles under lateral loading in cohesionless soils. The piles were tested in two different areas at the same site. Both areas consisted of a 3-m thick compacted superficial fill of pure fine sand, underlain by layers of naturally occurring pure fine-thick sand. Fills are differentiated by the relative densities which were compressed, 45% e 70%, respectively. Each area received one identical pair of cfa piles and two identical pairs of H-piles. A static lateral loading test was performed in each pair of piles. In this work, the pile load test results are reported and interpreted. The horizontal coefficient of subgrade reaction was determined from the results of the loading tests and compared with values determined by correlations based on penetration resistance index of SPT tests (NSPT). p-y formulations describing the static behavior of the piles were applied to the problem under evaluation. Back Analyses were made through theoretical and experimental p-y curves for obtaining input parameters for the analytic models, among which the coefficient of horizontal reaction. The soil pile system horizontal loading at rupture was determined by the theoretical methods and the results were compared with the experimental results, checking its validity